The Emerald handbook of multi-stakeholder communication : emerging issues for corporate identity, branding and reputation - Nguyen, Bang; Melewar, T. C.; Foroudi, Pantea (Emerald Publishing Limited, 2022)
The Emerald Handbook of Multi-Stakeholder Communicationgathers an international, multidisciplinary team of experts to explore effective brand messaging for multiple stakeholders, utilizing a diverse array of theoretical and methodological approaches that cumulatively present an up-to-date overview of the whole field.- Resumé vydavatel